Integrated epigenomic and transcriptomic analysis reveals TP63 as a novel player in clinically aggressive chronic lymphocytic leukemia - Papakonstantinou, Nikos; Ntoufa, Stavroula; Tsagiopoulou, Maria; Moysiadis, Theodoros; Bhoi, Sujata; Malousi, Andigoni; Psomopoulos, Fotis; Mansouri, Larry; Laidou, Stamatia; Papazoglou, Despoina; Gounari, Maria; Pasentsis, Konstantinos; et al. (International journal of cancer, 2019)
Chronic lymphocytic leukemia (CLL) stereotyped subsets #6 and #8 include cases expressing unmutated B cell receptor immunoglobulin (BcR IG) (U-CLL). Subset #6 (IGHV1-69/IGKV3-20) is less aggressive compared to subset #8 (IGHV4-39/IGKV1(D)-39) which has the highest risk for Richter's transformation among all CLL. The underlying reasons for this divergent clinical behavior are not fully elucidated. To gain insight into this issue, here we focused on epigenomic signatures and their links with gene expression, particularly investigating genome-wide DNA methylation profiles in subsets #6 and #8 as well as other U-CLL cases not expressing stereotyped BcR IG. We found that subset #8 showed a distinctive DNA methylation profile compared to all other U-CLL cases, including subset #6. Integrated analysis of DNA methylation and gene expression revealed significant correlation for several genes, particularly highlighting a relevant role for the TP63 gene which was hypomethylated and overexpressed in subset #8. This observation was validated by quantitative PCR, which also revealed TP63 mRNA overexpression in additional nonsubset U-CLL cases. BcR stimulation had distinct effects on p63 protein expression, particularly leading to induction in subset #8, accompanied by increased CLL cell survival. This pro-survival effect was also supported by siRNA-mediated downregulation of p63 expression resulting in increased apoptosis. In conclusion, we report that DNA methylation profiles may vary even among CLL patients with similar somatic hypermutation status, supporting a compartmentalized approach to dissecting CLL biology. Furthermore, we highlight p63 as a novel prosurvival factor in CLL, thus identifying another piece of the complex puzzle of clinical aggressiveness.
Keywords: Apoptosis; DNA Methylation; nádorové buňky kultivované; Transcription Factors; promotorové oblasti (genetika); Epigenomics; Gene Expression Profiling; Tumor Suppressor Proteins; metylace DNA; Sequence Analysis, RNA; Primary Cell Culture; regulace genové exprese u nádorů; transkripční faktory; lidé; RNA, Small Interfering; Tumor Cells, Cultured; Gene Expression Regulation, Neoplastic; Up-Regulation; Female; apoptóza; malá interferující RNA; nádorové supresorové proteiny; upregulace; chronická lymfatická leukemie; primární buněčná kultura; Male; ženské pohlaví; Humans; mužské pohlaví; Promoter Regions, Genetic; epigenomika; receptory antigenů B-buněk; sekvenční analýza RNA; Leukemia, Lymphocytic, Chronic, B-Cell; stanovení celkové genové exprese; Receptors, Antigen, B-Cell